2008
DOI: 10.1021/ja7114508
|View full text |Cite
|
Sign up to set email alerts
|

Global Molecular Structure and Interfaces:  Refining an RNA:RNA Complex Structure Using Solution X-ray Scattering Data

Abstract: We demonstrate in this report that solution X-ray scattering data can be utilized to precisely define the global structure and, therefore, implicitly the interfaces of an RNA:RNA complex. Defining the interfaces among components and the global structure of multicomponent systems is one of the essential problems in understanding biological interactions on a molecular level. However, identifying molecular interfaces is not an easy task for solution NMR spectroscopists. To resolve this problem, a widely used prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 18 publications
1
75
0
Order By: Relevance
“…5B), EcRapA-TtCore, and EcRapA⌬N-TtCore (Fig. 6B) are also in good agreement with those calculated from experimental data as judged on the basis of previous studies (36,37). Furthermore, we show here that SAXS can be used to complete large, multisubunit structures with missing components.…”
Section: Discussionsupporting
confidence: 90%
“…5B), EcRapA-TtCore, and EcRapA⌬N-TtCore (Fig. 6B) are also in good agreement with those calculated from experimental data as judged on the basis of previous studies (36,37). Furthermore, we show here that SAXS can be used to complete large, multisubunit structures with missing components.…”
Section: Discussionsupporting
confidence: 90%
“…Recent success with combining NMR and SAXS/WAXS data for refining structural ensembles [32,[45][46][47] has shown that inclusion of global restraints is functionally complementary and successful for NMR structure solution, and our work shows that pump-probe X-ray scattering measurements have decisive value for time-resolved structure determination when used in combination with additional experimental restraints from DEER and NMR. b Ramachandran analysis was conducted on the calculated average structure from the ensemble using Molprobity (http://molprobity.biochem.duke.edu/).…”
Section: Interspin Distance and Distance Distribution Changes In The mentioning
confidence: 77%
“…It is made available under a The copyright holder for this preprint (which was . http://dx.doi.org/10.1101/098723 doi: bioRxiv preprint first posted online Jan. 6, 2017; In the GAAA tetraloop receptor dimers (Table S19), the A:A W:W Trans pair is a part of A:A-U triple that mediates binding of the hairpin GAAA loop of one monomer with the receptor internal loop of the other ( Figure 11F) [79][80][81] . In HIV dimerization initiation site (Context 1 of Table S20) the dimerization of two monomers takes place via a kissing loop interaction 82 .…”
Section: Role Of A:g W:w Trans Type Recurrent Hydrogen Bonded Interacmentioning
confidence: 99%